2019
DOI: 10.1177/1076029619896621
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin Levels in Patients With Chronic Kidney Disease Stage 5 on Hemodialysis Directly Correlate With Intact Parathyroid Hormone and Alkaline Phosphatase

Abstract: Chronic kidney disease stage 5 (CKD5) marks the fifth stage of renal failure, frequently causing dysregulation of bone and mineral metabolism. Challenges exist in evaluating and managing chronic kidney disease–mineral bone disorder (CKD-MBD) with the standard panel of biomarkers. Our objective was to profile osteopontin (OPN) in patients with CKD5 on maintenance hemodialysis (CKD5-HD) and elucidate its relationship to phosphorus (P), calcium (Ca2+), alkaline phosphatase (AP), and intact parathyroid hormone (iP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
2
4
0
Order By: Relevance
“…The current study findings are consistent with previous studies in CKD showing elevated OPN serum levels mainly in the adult population with CKD (Druck et al, 2019;Barreto et al, 2011) [25] [26] some studies have related high circulating levels of OPN to adverse cardiovascular events in the general population (Waller et al, 2010) [23] and in CKD patients (Lamort et al, 2019) [27].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The current study findings are consistent with previous studies in CKD showing elevated OPN serum levels mainly in the adult population with CKD (Druck et al, 2019;Barreto et al, 2011) [25] [26] some studies have related high circulating levels of OPN to adverse cardiovascular events in the general population (Waller et al, 2010) [23] and in CKD patients (Lamort et al, 2019) [27].…”
Section: Discussionsupporting
confidence: 93%
“…In addition, in the current study, we found a strong correlation between osteopontin and PTH. This is consistent with a recent study by (Druck et al, 2019) [25]. Indeed osteopontin may play an essential role in vascular calcification OPN knockout mice have been shown to have higher bone formation secondary to PTH-induced increase in osteoblast activity, and PTH infusion has been shown to increase OPN levels.…”
Section: Discussionsupporting
confidence: 93%
“…In a study of patients on maintenance hemodialysis, OPN levels were found to have significant positive correlations with intact parathyroid hormone, indicating that OPN may play an integral role in the mineral bone disorder axis. As such, the data suggest that it may be important to monitor OPN when managing patients on maintenance hemodialysis [124].…”
Section: End Stage Renal Disease (Esrd)mentioning
confidence: 99%
“…Knowledge of these approaches can potentially drive therapies targeting OPN and ntOPN in CKD (Figure 3). As such, the data suggest that it may be important to monitor OPN when managing patients on maintenance hemodialysis [124].…”
Section: Therapeutic Approaches To Modulate Opn Expression and Functionmentioning
confidence: 99%
“…One study indicated that circulating levels of flOPN were closely related to GFR and CV risk markers in patients with CKD [42]. Elevated plasma flOPN was also reported in a cohort of patients with CKD stage 5 receiving hemodialysis (CKD 5-HD) compared to a normal healthy cohort [43]. Further, a significant positive correlation of flOPN with iPTH and alkaline phosphatase was observed in CKD 5-HD patients [43].…”
Section: Discussionmentioning
confidence: 99%